To talk or not to talk: A review of situational antecedents of willingness to communicate in the second language classroom. (February 2018) - Zhang, Jiayi; Beckmann, Nadin; Beckmann, Jens F.
Abstract: Willingness to communicate (WTC) used to be seen as a stable, trait-like communicative tendency; however, in the field of second language acquisition (SLA), attention has recently shifted to its more dynamic, state-like components. This article systematically reviews the literature on the situational antecedents that might contribute to variation in WTC. It aims specifically at furthering our understanding of the interaction between WTC and the learning situation. After searching major databases (Web of Science, ERIC and the British Education Index), findings of 35 studies were analyzed. Different kinds of situational antecedents of WTC suggested in these studies were then systematically organized into a multi-layered framework. The framework raises awareness of the role of the learning situation, and how the learning situation is perceived by second language learners. The framework has the potential to guide future research by offering a more comprehensive and systematic approach to the study of situational antecedents of WTC and the dynamic processes that underpin WTC.